Semangat Anti Korupsi dalam Moderasi Beragama (Studi Komparatif Agama Islam dan Kristen) - Ashri, Zainul; Lalu Riastata Al Mujaddi (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2024)
Corruption is a deviant act in social life, culture, especially in religion. The act is seen as a misuse and abuse of power or position and betrayal of trust. The phenomenon of corruption has become ingrained in a country, and Indonesia is no exception. Therefore, what is the concept of corruption according to Islam and Christianity?. With aliteratur study and comparative analysis, this research found: Islam views corruption as 1). Akhdzul amwal bil bathil, which is eating other people’s wealth unlawfuly, 2). Al-gulul, which is betrayal or misappropriation, 3). Al-Suhtu, which is the proceeds of an unlawful act, 4). Risywah, or bribery. Christianity views corruption as theft, an act of moral corruption, self-enrichment, and abuse of authority. As for addressing this, Islam gives the sancition of cutting hands to corruptors, while Christianity sanctions corruption with compensation twice as much as what stolen or corrupted.